Analisis Peran Guru Dalam Meningkatkan Minat Belajar Matematika Siswa Kelas 3 Di Mi Islamiyah Kedungmegarih - Sa'adah, nikmatus; Sholihah, Mufidatus; Mutmainah, Siti; Lailatul Arofah, Nur (Jurnal Murid, 2024)
The purpose of this study was to analyze the interest in learning mathematics and the teacher's role in increasing the interest in learning mathematics for grade 3 students at MI Islamiyah Kedungmegarih. The approach used in this research is a qualitative approach and a descriptive research type. The data sources in this study is headmaster, grade 3 math teachers and grade 3 students. The data collection techniques were carried out through the stages of observation, interviews and documentation. Data analysis was carried out through three activity lines: data reduction, data presentation and drawing conclusions. Based on the findings in the field, that there are more grade 3 students who have high interest than those who have moderate and low interest in mathematics. The role of the teacher given in increasing interest in learning mathematics for grade 3 students at MI Islamiyah is (1) The teacher is the manager. (2) Teachers as guides. (3) The teacher as a facilitator. (4) The teacher as evaluator. (5) The teacher as a motivator.